Pengaruh Transportasi Online Terhadap Penyerapan Tenaga Kerja Di Kota Kupang - Bernadinus Yohanes Loda; Cicilia A. Tungga; Fransina W. Ballo (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research aims to determine the effect of online transportation on labor absorption in Kupang City. This research was conducted on online application drivers in Kupang City, namely Grab, Maxim and InDrive. The number of samples studied was 32 respondents. This research uses a quantitative research approach. The sampling technique for this research uses a non-probability technique, namely the incidental sampling technique. Data analysis used in quantitative methods is validity testing, reliability testing, simple linear regression, and hypothesis testing using the Statistical Package for Social Science 26.0 for Windows (SPSS 26) tool. The test results show that the online transportation variable has an effect on labor absorption. Other findings show that online transportation simultaneously influences labor absorption with a coefficient of determination of 68.6%.